Elementy magii i religii w rzeczywistości społecznej kapitalizmu - Kufliński, Mateusz (Kultura-Społeczeństwo-Edukacja, 2022)
The article is dedicated to the issue of magic and religion in the social reality of capitalism. The goal of the article is to present examples proving that capitalism in various places (post-communist Central Europe, San Cristobal in the Mexican state of Chiapas, Colombian department Valle del Cauca, New York) and at various times (from the 1970s to the second decade of the 21st century) was associated with elements of religion and magic through social thinking and practice, and therefore elements of social reality. On the other hand, in the discourse, capitalism is often presented as a part of nature: the existence that acts objectively, like the laws of physics. In the article, this apparent contradiction is presented as a dialectical aspect of the present day, in which the discourse and social reality are complementary.